Median Nerve Compression in Carpal Tunnel Caused by a Giant Lipoma - F. Fazilleau; T. Williams; J. Richou; V. Sauleau; D. Le Nen (Case Reports in Orthopedics)
A lipoma is a common, benign soft-tissue tumor that rarely arises in the upper limb. When one does occur in the hand, the location of the lipoma can cause nerve compression, which can mimic carpal tunnel symptoms. Magnetic resonance imaging is the visualization modality of choice for diagnosis and surgical planning of lipomas. Surgical resection is recommended to relieve the neurological manifestations of this disease. The surgeon should always suspect liposarcoma first before voluminous, atypical, or recurrent tumors are considered.